Antifungal Activity of Lipopeptides From Bacillus XT1 CECT 8661 Against Botrytis cinerea - Toral, Laura; Rodríguez, Miguel; Béjar, Victoria; Sampedro, Inmaculada (Frontiers in Microbiology, 2018)
This work aims to explore the capacity of a Bacillus methylotrophicus (later heterotypic synonym of Bacillus velezensis) strain named XT1 CECT 8661 against the necrotrophic plant pathogen Botrytis cinerea and to identify the compounds responsible for its activity. Q_TOF electrospray mass spectrometry analysis allow us to detect several lipopeptides -surfactin, bacillomycin, and fengycin- in XT1 cultures. In vitro antibiosis studies demonstrated the efficiency of the lipopeptide fraction for the inhibition of fungal growth. In fact, microscopy studies (SEM/TEM) revealed, an alteration of the morphology of the phytopathogen in interaction with lipopeptides, with resistance structures appearing in the early stages of growth of the fungus. Our studies, carried out with tomatoes, grapes and strawberries have demonstrated the efficiency of Bacillus XT1 CECT 8661 lipopeptides against B. cinerea infection and it capability to trigger the antioxidant activity in fruit. Overall, the results of this study highlight the potential of lipopeptides of this strain as an effective biological control agent against the colonization of B. cinerea.